2014
DOI: 10.1186/1471-2458-14-949
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported cataracts in older adults in Ghana: sociodemographic and health related factors

Abstract: BackgroundChanges in function of sensory organs with increasing age have significant impact on health and wellbeing of older persons. This paper describes cataract, a chronic eye condition, self-reported among older adults in Ghana and the need for improving access to eye care services.MethodsThis work was based on the World Health Organization’s multi-country Study on global AGEing and adult health (SAGE), conducted in six countries including Ghana. SAGE Wave 1 in Ghana was conducted in 2007–2008 in a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 23 publications
9
26
2
Order By: Relevance
“…Unexpectedly, we found men who smoked often had obviously lower prevalence of cataract than those who never smoked (2.81% versus 3.61%). Such paradoxical result has also been presented in other studies [ 43 ]. To find the reason, we further analyzed our data and found that individuals who smoked often were significantly younger than those who never smoked (69.45 years versus 71.78 years, P < 0.01), especially among men (69.12 years versus 71.77 years, P < 0.01).…”
Section: Discussionsupporting
confidence: 78%
“…Unexpectedly, we found men who smoked often had obviously lower prevalence of cataract than those who never smoked (2.81% versus 3.61%). Such paradoxical result has also been presented in other studies [ 43 ]. To find the reason, we further analyzed our data and found that individuals who smoked often were significantly younger than those who never smoked (69.45 years versus 71.78 years, P < 0.01), especially among men (69.12 years versus 71.77 years, P < 0.01).…”
Section: Discussionsupporting
confidence: 78%
“…Cataract is defined as partial or complete opacification of the crystalline lens and is considered the primary cause of vision loss worldwide (1).It is the leading cause of blindness accounting for nearly 48% of blindness globally (2). Although the actual mechanism of cataract development remains unclear, several risk factors have been established, including age, sunlight (UV) exposure ,corticosteroid use, trauma, hypertension, Diabetic Mellitus, and smoking, have resulted in a large public health burden (3).The studies also found higher prevalence of self-reported cataract among individuals with lower income, lower education, urban residency, female sex,, and intake of antidepressants (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the control variables was based on past literature. 30,31 These control variables are confounding factors and the obesity-…”
Section: Covariatesmentioning
confidence: 99%